PENGARUH PMR TERHADAP RESPON PSIKOLOGIS IBU MENJALANI NEW NORMAL DI MASA PANDEMI COVID 19 - Yusniar Yusniar (Jurnal Endurance, 2023)
The Covid-19 pandemic has caused fear in society. The Covid-19 outbreak has resulted in policies such as restricted social activities, working from home (WFH), isolation, lock down and restrictions on religious activities. This situation results in many negative stressors that can be experienced by mothers who work at home. This situation can be reduced with psychological intervention, relaxation exercises, breathing exercises and awareness exercises. Progressive muscle relaxation technique is a method of relaxing muscles aimed at reducing muscle tension with easy and systematic implementation by tensing the muscles and then relaxing them again. Quasi experiment without control group with one group pretest and posttest design is the type of research used. The research sample was 50 working mothers with children undergoing the new normal during the Covid-19 pandemic. Sampling was taken using purposive sampling technique. The data instrument used was the Depression Anxiety Stress Scale (DASS 21) questionnaire, which consists of 21 questions. Based on the Wilcoxon test statistical test, there is an effect of PMR on psychological responses (depression) with a p value of 0.000, there is an effect of PMR on psychological responses (anxiety) with a p value of 0.000, there is an effect of PMR on psychological responses (stress) with a p value of 0.000. PMR makes a positive contribution to overcoming the mother's psychological response during the new normal during the Covid 19 pandemic. Key Words : Covid-19 ; PMR; Moms are living the new normal